Estimating the Mediterranean sea-level trends from 1993 to 2022 showing the consistency of X-TRACK-L2P coastal altimetry with tide gauge data and trend impacts on Egypt's northern coast - Youssef, Mohamed M.; Li, Qianqian; Zaki, Ahmed; Wu, Lin; Bao, Lifeng (Frontiers in Marine Science, 2025)
In recent decades, sea level has risen markedly along Mediterranean coastlines, highlighting the growing impacts on vulnerable coastal regions. This study analyzed sea-level variability using tide gauge (TG) records from 45 stations, coastal altimetry data (X-TRACK-L2P and X-TRACK/ALES), and virtual altimetry station (VAS) data. Based on TG records from 1993 to 2022, the results reveal positive linear trends, with 11 stations recording rates well above the global mean. The highest rate, 5.281 mm/year, was observed at TARANTO (Station ID: 2095). Strong consistency was also found between TG and X-TRACK-L2P coastal data, with X-TRACK-L2P trends ranging from −3 to 6 mm/year. In addition, sea-level rise in the Adriatic, Aegean, and Levantine sub-basins exceeded the current global mean. The agreement between TG and X-TRACK/ALES data was more limited, observed at only two sites located about 7 km and 20 km apart from the first valid point on the altimetry track, respectively. Furthermore, the findings highlight the diverse impacts of sea-level rise on Egypt's northern coast, where densely populated areas, productive agricultural lands, and cultural heritage sites are particularly at risk. In conclusion, all types of data used indicate positive linear trends in the Mediterranean Sea. In addition, several sites have rates of sea-level trend that exceed the global mean, underscoring the urgent need for proactive adaptation measures.